Thematic Roles Assigned to Subject Argument in Minangkabau Passive Voice - widya, widya; Agustiana, Erika (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
The category of voice allows speakers to view an event or situation from a variety of perspectives by examining the relationship between the verb's action or state and the participants defined by its arguments, such as subject and object. The purpose of this study was to identify the thematic roles assigned to subject argument passive diathesis in Minangkabau. The sorts of thematic roles assigned to subject position in passive voice were recognized and evaluated. This descriptive qualitative research was carried out using the research phases of (1) data collection, (2) data analysis, and (3) result presentation. The data was gathered from written source that is the novel Padati Ajo Dindin written by Ajo Flamboyan (2020) and oral sources in Minangkabau dialect. Thematic roles assigned to subject position in Minangkabau passive voice are PATIENT, THEME, STIMULUS, RECIPIENT, and BENEFICIERY, according to research findings, and they apply to all varieties of passive in Minangkabau, including passive with the prefix di-, ta-, or ba-.